2022
DOI: 10.1039/d2nr03632k
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the key molecules involved in the green synthesis of nanoparticles

Abstract: Emerging nanotechnology offers great interest and success in synthesizing and applying nanoparticles (NPs) using the green-chemistry approach. Since NPs synthesized using naturally derived materials are a potential alternative compared to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 157 publications
0
20
0
Order By: Relevance
“…Emerging nanotechnology, notably the use of nanoparticles in managing a wide spectrum of bacterial pathogens, has emerged as a promising strategy . Nanoparticles’ features, such as small size, large surface area, biocompatibility, and targeting to specific sites, make them more suited for use in various biochemical functions. , Most studies used biologically derived raw materials (from algae, fungi, bacteria, and mammals) to synthesize organic or inorganic nanoparticles to treat infectious and noninfectious diseases due to their various benefits over chemically synthesized nanoparticles. We synthesize two different kinds of metallic nanoparticles, such as silver (AgNPs) and gold (AuNPs), using microbial-derived products as raw materials, which have several advantages. According to a recent study, probiotics, particularly lactic acid bacteria (LAB), have drawn much interest from the food and pharmaceutical industries because of their many advantages for human health and well-being. Several studies have shown that LAB provides biological protection against microbial infections. , As a result, it would be one of the novel approaches to using LAB as an environmentally friendly method of synthesizing biocompatible NPs that can be used to treat a wide variety of microbial infections. , Thus, in the current study, we sought to isolate and characterize the LAB strains from the Kimchi sample as a biological source for the synthesis of AuNPs and AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging nanotechnology, notably the use of nanoparticles in managing a wide spectrum of bacterial pathogens, has emerged as a promising strategy . Nanoparticles’ features, such as small size, large surface area, biocompatibility, and targeting to specific sites, make them more suited for use in various biochemical functions. , Most studies used biologically derived raw materials (from algae, fungi, bacteria, and mammals) to synthesize organic or inorganic nanoparticles to treat infectious and noninfectious diseases due to their various benefits over chemically synthesized nanoparticles. We synthesize two different kinds of metallic nanoparticles, such as silver (AgNPs) and gold (AuNPs), using microbial-derived products as raw materials, which have several advantages. According to a recent study, probiotics, particularly lactic acid bacteria (LAB), have drawn much interest from the food and pharmaceutical industries because of their many advantages for human health and well-being. Several studies have shown that LAB provides biological protection against microbial infections. , As a result, it would be one of the novel approaches to using LAB as an environmentally friendly method of synthesizing biocompatible NPs that can be used to treat a wide variety of microbial infections. , Thus, in the current study, we sought to isolate and characterize the LAB strains from the Kimchi sample as a biological source for the synthesis of AuNPs and AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the green technique for nanoparticle synthesis offers significant benefits over the chemical-based technique [ 13 ]. Green synthesis NPs have several benefits over chemical and physical approaches, including being easier to synthesize, eco-friendly, cost-effective, minimizing the release of harmful compounds into the environment, and producing stable and biocompatible NPs [ 14 , 15 ]. There are more and more reports on the production of nanoparticles from biologically derived materials such as plants, algae, fungi, bacteria, and animals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles, particularly metallic ones, have been widely used in the treatment of microbial pathogens due to several advantages, including specific targeting, an effective drug delivery system, less cytotoxicity, and controlled release [ 22 , 23 , 24 ]. A growing number of research studies has focused on using naturally occurring substances from plants, algae, fungi, bacteria, or animals in the synthesis of metallic nanoparticles [ 25 , 26 ]. The use of marine-derived materials in the synthesis of nanoparticles has received particular attention due to their ease of availability, low cost in the isolation of active molecules, biocompatibility, biodegradability, and potential bioactive properties [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%